The simulation results of the high-pass and low-pass filter effect on the quality of micropotential recordings on the electrocardiogram; Biology and Medicine; Vol. 6, iss. 1 - Avdeeva D. K. Diana Konstantinovna; Kazakov V. Yu. Veniamin Yurevich; Natalinova N. M. Nataliya Mikhailovna; Ivanov M. L. Maxim Leonidovich; Yuzhakova M. A. Maria Aleksandrovna; Turushev N. V. Nikita Vladimirovich (2014, 2014)
Title screen